Mandat Ilahi tentang Memberitakan Kerajaan Allah - Lucky Antonio (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The divine mandate given to man by God from the very beginning of creation was to rule the world (Gen. 1:27). The foundation of God’s Kingdom has already existed since its creation. After man fell into sin, there was enmity between the serpent, the women, and their respective offspring (Gen. 3:6-7). God’s promise that the serpent will be crushed pointed to the coming of the Messiah and the assurance of victory (Gen. 3:15). The divine mandate to proclaim the kingdom of God can not be hindered by anyone and needs to be known by every believer. Therefore, every believer is called to fulfill God’s plan to proclaim the kingdom of God. To find out the divine mandate for preaching God’s Kingdom, the qualitative method of literature study is used. AbstrakMandat ilahi diberikan Allah kepada manusia sejak awal penciptaan adalah menguasai dunia (Kej. 1:27). Dasar tentang kerajaan Allah juga sudah ada sejak penciptaan. Setelah manusia jatuh dalam dosa, terjadilah permusuhan antara si ular dengan perempuan, dan keturunan masing-masing (Kej. 3:6-7). Janji Allah bahwa ular itu akan diremukkan menunjuk kepada kedatangan Mesias dan jaminan kemenangan, (Kej.3:15). Mandat ilahi tentang memberitakan kerajaan Allah tidak bisa dihalangi oleh siapapun dan perlu diketahui oleh setiap orang percaya. Oleh sebab itu orang percaya terpanggil untuk menggenapi rencana Allah yaitu memberitakan kerajaan Allah. Untuk mengetahui mandat ilahi tentang memberitakan kerajaan Allah, maka dalam penulisan menggunakan metode kualitatif yaitu studi literatur atau studi pustaka.